2015
DOI: 10.7603/s40680-015-0021-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different physiotherapy interventions on the activities of daily living and the quality of life in children with cerebral palsy

Abstract: Amaç: Bu çalışmanın amacı Serebral Palsili (SP) bireylerde nörogelişimsel tedavi programına (NGT) ek olarak uygulanan kinezyoteyp (KT) ve nöromüsküler elektrik stimülasyonu (NMES) uygulamaları-nın günlük yaşam aktiviteleri ve yaşam kaliteleri üzerine etkilerini araştırmaktır.Yöntemler: Çalışmaya yaşları 5-12 arasında değişen, SP tanısı almış, kaba motor fonksiyon sınıf-lama sistemi (KMFSS)'ne göre 3-4-5 seyiyesinde toplam 45 çocuk dahil edildi. Çocuklar 3 gruba ayrıldı; 1. gruba NGT uygulandı, 2. gruba NGT ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In general, physiotherapy interventions that sought to improve the function and strength of the trunk and lower extremities in children with CP thereby improving activity, functional ability, and social participation are likely to improve their QOL [34,35]. Furthermore outcomes of researches have shown that QOL in children with CP could increase with the improvement in physical, social and psychological wellbeing [36], mobility and the ability to perform self-care activities [37].…”
Section: Discussionmentioning
confidence: 99%
“…In general, physiotherapy interventions that sought to improve the function and strength of the trunk and lower extremities in children with CP thereby improving activity, functional ability, and social participation are likely to improve their QOL [34,35]. Furthermore outcomes of researches have shown that QOL in children with CP could increase with the improvement in physical, social and psychological wellbeing [36], mobility and the ability to perform self-care activities [37].…”
Section: Discussionmentioning
confidence: 99%